Renaissance of Third-Tier Cities Through In-Migration?: Assumptions from' Trial Residencies' in Görlitz. Issue 1 (2nd January 2020) - Knippschild, Robert; Rößler, Stefanie; Zöllter, Constanze
Abstract: When a city in a peripheral location has shrunk dramatically over recent decades, what potential does it have to keep or attract residents over the long term? Could testing life in new locations for a limited period help identify urban strengths and weaknesses, which can then be exploited for future development? The 'Probewohnen – Trial residencies' project gave interested persons the chance to experience daily life in the historic centre of the German city of Görlitz for a week. Scientific surveys provided information on the expectations and experiences of the project participants. The results show that third-tier cities with good infrastructure and a historic building stock have great potentials as future residential hubs.